Endocrine disrupting chemicals exposure and health: An umbrella review - Junhao Chen; Pan Song; Chao Li; Hengjia Liu; Lei Zhang; Yi Zhou; Zhien Zhou; Weigang Yan (Ecotoxicology and Environmental Safety, 2025)
The aim of this umbrella review was to evaluate the quality, potential biases, and validity of the existing evidence on the relationship between endocrine disrupting chemicals (EDCs) exposure and health outcomes, through a comprehensive review of available meta-analyses. The included meta-analyses were searched across multiple databases, including PubMed, Embase, and Web of Science. This umbrella review included systematic reviews and meta-analyses of randomized controlled trials, cohort studies, case-control studies, and cross-sectional studies that assessed the impact of EDCs exposure on various health outcomes in humans. The search resulted in the identification of 67 meta-analyses and 109 health outcomes from 7552 unique articles. All of these 109 health outcomes were derived from meta-analyses of observational studies. EDCs exposure included pesticides (n = 30), BPA (n = 13), PAHs (n = 18), PFAS (n = 10), and heavy metals (n = 38). Sixty-nine harmful associations were found to be statistically significant, along with one beneficial association. The remaining 39 outcomes were either harmful or beneficial but did not reach statistical significance. Significant harmful associations between EDCs exposure and 22 cancer outcomes, 21 neonatal/infant/child-related outcomes, 18 metabolic disorder outcomes, 17 cardiovascular disease outcomes, 11 pregnancy-related outcomes, and 20 other outcomes (renal, neuropsychiatric, respiratory, and hematologic) were detected. Exposure to environmental EDCs is closely linked to a wide range of adverse health outcomes. Given the widespread exposure to these pollutants globally, precautionary policies may be warranted to reduce population-level exposure and mitigate potential health risks associated with environmental chemicals.